2020
DOI: 10.1002/oa.2914
|View full text |Cite
|
Sign up to set email alerts
|

The tooth of a giant sea creatureOtodus(Megaselachus) in the material culture of Neolithic maritime hunter‐gatherers at Sharbithat (Sultanate of Oman)

Abstract: A mega-tooth belonging to a Miocene fossil shark was discovered along the shores of the Arabian Sea inside one of the Neolithic domestic settlements at Sharbithat (SHA-10) (Sultanate of Oman). Attributed to a representative of the extinct genus Otodus (Megaselachus), this tooth is the first ever discovered in the Arabian Peninsula. In the field, research permitted the localization and study, a few kilometres away, of the palaeontological deposit where this retrieval was made. The shark, traditionally extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Instead the presence of these teeth may reflect collection for other cultural purposes (tools, pendants, etc. ), as has been observed in different contexts worldwide (Cione and Bonomo, 2003;Betts et al, 2012;Charpentier et al, 2020). Alternatively, the fossils were simply a component of the local soil substrate and derive from weathering processes of the Late Cretaceous limestone substrate.…”
Section: Assessing Post Mortem Diagenetic Alteration and Fish Provenancementioning
confidence: 75%
See 1 more Smart Citation
“…Instead the presence of these teeth may reflect collection for other cultural purposes (tools, pendants, etc. ), as has been observed in different contexts worldwide (Cione and Bonomo, 2003;Betts et al, 2012;Charpentier et al, 2020). Alternatively, the fossils were simply a component of the local soil substrate and derive from weathering processes of the Late Cretaceous limestone substrate.…”
Section: Assessing Post Mortem Diagenetic Alteration and Fish Provenancementioning
confidence: 75%
“…While shark vertebrae centra are commonly found and usually well preserved, shark teeth are rarely recovered, even when the soil is carefully sieved (Table 1 and references therein). Interestingly, previous studies (Cione and Bonomo, 2003;Betts et al, 2012;Charpentier et al, 2020) determined that fossil shark teeth recovered from archaeological contexts have been employed as ornaments and tools, while shark vertebrae centra are only rarely identified as jewelry (Boulanger et al, 2020) and are usually interpreted as food remnants.…”
Section: Fish As a Commoditymentioning
confidence: 99%
“…1), some 4.6km to the east-northeast of the archaeological area where prehistoric collectors lost/left a damaged fossil tooth of Otodus (Megaselachus) cf. chubutensis 5,500 years ago (Charpentier et al, 2020). This ancient human collecting, and transportation testify that the fossils outcropping in SHA-34 were already spotted by Neolithic maritime hunter-gatherers, at least as for the large teeth of the great mega-toothed shark O.…”
Section: Introductionmentioning
confidence: 79%
“…chubutensis. Charpentier et al, (2020) identified a dozen of other fish species, including very well-preserved teeth of O. (Megaselachus) chubutensis, among the hundred specimens they collected at SHA-34.…”
Section: Introductionmentioning
confidence: 99%
“…Courtesy of the Iiyama City Board of Education. Shark hunting was carried out by prehistoric societies worldwide (Charpentier et al, 2020), possibly including the Jōmon, for whom social prestige may have been symbolised by shark teeth (Nakazawa, 2017;Watanabe, 1990). Evidence from fishhooks (Tajima, 2015) and stable carbon and nitrogen isotope analysis of human remains (Kusaka et al, 2010) supports the consumption of hightrophic-level fish in the Inland Sea area during the Late-Final Jōmon.…”
Section: Fig 2 Photograph Of a Jōmon Potsherd Frommentioning
confidence: 99%